Three-dimensional displacement mapping of diffused Pt thermal barrier coatings via synchrotron X-ray computed tomography and digital volume correlation. (1st April 2016) - Khoshkhou, D.; Mostafavi, M.; Reinhard, C.; Taylor, M.P.; Rickerby, D.S.; Edmonds, I.M.; Evans, H.E.; Marrow, T.J.; Connolly, B.J.
Abstract: A progressive study of the three-dimensional deformation field within a γ/γ′ thermal barrier coating following cyclic oxidation at 1200 °C is presented, observed using synchrotron X-ray micro-computed tomography and analysed by digital volume correlation. Oxide thickening and bond coat creep displacements are quantified as a function of exposure time at temperature. Linear gradients of these displacements are measured both in-plane and normal to the oxide layer. The first thermal cycle shows the most displacement changes; destructive sectioning confirms the DVC-calculated displacement magnitudes. Graphical abstract: